QUALIMETRIC EVALUATION OF THE MOСНI FROZEN DESSERTS MADE USING BY-PRODUCTS OF JUICE PRODUCTION - Lapytska, Надія; Rybalochko, Олена; Kavurko, Діана (Biota. Human. Technology, 2025)
The work is devoted to the qualimetric evaluation of the quality of Mochi frozen desserts using by-products of juice production as a fruit filling. The by-products of juice production, which are proposed to be used in the presented studies, are apple and blueberry extracts. They accumulate to a large extent in canneries and restaurants. In the vast majority of squeezes, they are disposed of, causing economic losses to enterprises and negatively affecting the environment by polluting it. Only 8 % of such by-products are further processed in compound feed plants and for the production of pectin. However, pomace has significant potential as an enriching raw material for the production of health products, as they have a chemical composition rich in dietary fibers, vitamins and minerals. The use of pomace in the production of Mochi frozen desserts will allow to obtain functional products with added value thanks to the complex processing of raw materials. The introduction of non-traditional fortifying raw materials can significantly affect not only the nutritional value of desserts, but also their quality. Therefore, for a comprehensive assessment of the quality of frozen desserts, a “property tree” has been developed, which includes organoleptic, physico-chemical and structural-mechanical quality indicators, as well as nutritional and energy value. The weighting coefficients of individual and group properties are determined. According to the developed “property tree”, a qualitative assessment of the quality of Mochi frozen desserts was carried out. The purpose of the article – comprehensive evaluation of the quality of Mochi frozen desserts made using the by-products of juice production as a filling component and guar gum as a rice dough stabilizer, using the principles of qualimetry. Methodology. During the work, we used physico-chemical, organoleptic research methods, principles of qualimetry that take into account individual and group qualities of the developed products. Results were processed using MC Excel databases. The scientific novelty is that the application of the principles of qualimetry established the effectiveness of adding 10 % of guar gum to the weight of rice flour to prevent the loss of structural and mechanical properties of Mochi dessert dough during freezing and thawing. The expediency of using apple and blueberry juice for enriching Mochi frozen desserts and providing them with added value due to complex processing of raw materials has also been established. Conclusions: a “property tree” of Mochi frozen desserts was developed. On the basis of the compiled “property tree”, a comprehensive assessment of the quality of the developed products was carried out using apple or blueberry pomace as a fruit component of the filling and guar gum as a rice dough structure stabilizer. Based on the conducted qualitative assessment of quality, Mochi frozen desserts are recommended for production, the dough of which will contain 10 % of guar gum by mass of rice flour. At the same time, it is recommended to use both apple and blueberry pomace as a fruit component for the filling. In addition, the developed "property tree" can be used in the future for a comprehensive assessment of the quality of frozen desserts based on dairy and fruit raw materials with the use of various enrichment additives.